Development and evaluation of tofacitinib transdermal system for the treatment of rheumatoid arthritis in rats. (3rd June 2021) - Li, Yanmei; Sun, Yonghua; Wei, Shitong; Zhang, Luyang; Zong, Shihua
Abstract: Context: Tofacitinib tablet is approved for the treatment of rheumatoid arthritis (RA). However, tofacitinib (Tfc) faces extensive first-pass metabolism following oral administration. Aim: To develop transdermal systems of Tfc and evaluate their efficacies against RA using Freund's Complete Adjuvant immunized arthritis rat model. Methods: These systems were prepared by solvent casting method and evaluated for texture, needle strength, skin penetrability, in vitro drug release, skin permeation, stability, and in vivo anti-arthritic activity. Results and discussion: Transdermal patch (TS) showed smooth texture, good mechanical strength, slow-release, and slow permeation through the skin. Microneedle array (MNS) showed good needle strength, with required skin penetrability. MNS and TS showed 95% and 24% drug release, and 82% and 12% drug permeation, respectively in 4 h. The developed systems were found to be stable for 90 days at very stressful conditions, that is, 40 ± 2 °C and 75 ± 5% RH. MNS and TS both reduced arthritic scores (at p  < 0.01 and p  < 0.001 level, respectively) and the level of inflammatory cytokines (at p  < 0.05 and p  < 0.01 level, respectively) significantly as compared to that of the drug solution (DS). MNS and TS were found to be effective in restoring histological alterations (annum, synovial hyperplasia, synovial constriction, and cartilage and articular erosions) toward normal. Conclusion: TS and MNS were found to be stable and effective for the treatment of arthritis and hence considered a good alternative for the treatment of RA with better clinical pertinence.